Optimalisasi Pemeliharaan Preventif dalam Menekan Biaya Overhead Pabrik pada Industri Makanan - Dinanti, Nanda Pricilia Dara; Aladawiyah, Robiah; Maulita, Aprilia Nifatul; Wulandari, Ririn; Syahwildan, Muhamad (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Factory Overhead Costs (FOC) significantly influence operational efficiency, particularly in the context of machine maintenance, which plays a critical role in ensuring uninterrupted production processes. This study aims to evaluate the effectiveness of preventive maintenance strategies integrated with digital technology at PT Unilever Indonesia Tbk. A quantitative descriptive approach was employed, utilizing data from the company's annual and sustainability reports for the 2022–2024 period. Samples were selected using purposive sampling, focusing on data relevant to machine maintenance costs. The analysis examined the proportion of maintenance costs within total FOC and assessed the impact of preventive strategies on reducing operational downtime and unplanned repair expenses. The findings reveal that the adoption of Internet of Things (IoT)-based technology for real-time machine condition monitoring led to a 20% reduction in repair costs and improved overall operational efficiency. Preventive maintenance also proved effective in minimizing the risk of unexpected breakdowns that disrupt production. The novelty of this study lies in the integration of digital technologies with preventive maintenance strategies to enhance cost efficiency. This approach offers valuable insights for companies in the Fast-Moving Consumer Goods (FMCG) sector and underscores the importance of strategic investment in maintenance technologies to strengthen long-term competitiveness